2019
DOI: 10.1177/0963689718823517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy for Unruptured Intracranial Aneurysm in Elderly Patients: Coiling, Clipping, or Conservative?

Abstract: An increasing number of unruptured intracranial aneurysms (UIAs) has been discovered in elderly patients in recent years, but the optimal treatment strategy for these patients remains controversial. We report our six-year experience treating UIAs in elderly patients (≥ 70 years old). A retrospective review was conducted of elderly patients who harbored UIAs treated by conservative observation, microsurgical clipping, or endovascular coiling between January 2009 and December 2014. The patients’ clinical and ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Similar to our results, Yang et al reported that there was no significant difference in symptomatic complication and clinical outcome between the two groups. 20) Jang et al also reported that the morbidity rate was higher in coiling group (4%) than in clipping group (1.78%). 9) Some previous reports revealed that surgery for elderly patients is more invasive and has significant high morbidity and mortality than coiling.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similar to our results, Yang et al reported that there was no significant difference in symptomatic complication and clinical outcome between the two groups. 20) Jang et al also reported that the morbidity rate was higher in coiling group (4%) than in clipping group (1.78%). 9) Some previous reports revealed that surgery for elderly patients is more invasive and has significant high morbidity and mortality than coiling.…”
Section: Discussionmentioning
confidence: 92%
“…Yang et al also reported that general complications including heart dysfunction and pneumonia occurred significantly higher in surgery group (21.4%) than in EVT group (4.69%, p=0.033). 20) We thought that invasiveness of surgery and longer operation and anesthesia time might be associated to these results. In addition, the rate of good functional outcome at 3 months was lower in clipping group (90.9%) than in coiling group (97.7%) even though there was no statistical significance (p=0.154).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aggressive treatment for UCAs in elderly patients with risk factors of aneurysm rupture should be considered positively. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%